1983
DOI: 10.1103/physrevc.28.2222
|View full text |Cite
|
Sign up to set email alerts
|

Proton capture cross section ofBe7and the flux of high energy solar neutrinos

Abstract: The low energy cross section for the Be(p,y) B reaction has been measured by detecting the delayed e particles from the 'B beta decay. Detailed discussion is presented of the analysis of the radioactive Be target including the use of two independent methods to determine the Be areal density. The direct capture part of the cross section is subtracted from the total cross section to deduce resonance parameters for the 1+ first excited state in B. The zero-energy astrophysical S factor inferred from the present e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
161
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(167 citation statements)
references
References 18 publications
6
161
0
Order By: Relevance
“…Very recently, the latter has been redetermined by new high-precision direct measurements [4,5,6,7] and extrapolated to zero energy with the help of a theoretical model [8]. The resulting zero-energy astrophysical S factors, S 17 (0), however, do not always agree within their quoted errors: Hammache et al [4] found S 17 (0) = 18.8 ± 1.7 eV b, in agreement with other direct-capture data [5,9,10]. In contrast, Junghans et al [6] report a considerably larger value, S 17 (0) = 22.3 ± 0.7 ± 0.5 eV b.…”
supporting
confidence: 62%
See 2 more Smart Citations
“…Very recently, the latter has been redetermined by new high-precision direct measurements [4,5,6,7] and extrapolated to zero energy with the help of a theoretical model [8]. The resulting zero-energy astrophysical S factors, S 17 (0), however, do not always agree within their quoted errors: Hammache et al [4] found S 17 (0) = 18.8 ± 1.7 eV b, in agreement with other direct-capture data [5,9,10]. In contrast, Junghans et al [6] report a considerably larger value, S 17 (0) = 22.3 ± 0.7 ± 0.5 eV b.…”
supporting
confidence: 62%
“…The opposite behaviour is noted above the M1 resonance: our data and those of Refs. [6,7] match excellently, whereas the other (p,γ) experiments [4,5,9,10] consistently report lower values. We want to emphasize the remarkably good agreement of our CD data up to 1.1 MeV with the most recent direct-proton-capture experiment where an ion- Ref.…”
mentioning
confidence: 50%
See 1 more Smart Citation
“…(1) uncertainties in the measured cross sections at laboratory energies, (2) The "average cross section" which they extrapolated to solar energies was obtained by averaging cross sections which differ by many standard deviations and have different energy shapes (the cross sections measured by Kavanagh (1960) and by Parker (1968) differ by more than 3σ from the cross sections measured later by Vaughn (1970) and by Filippone (1983) Dar and Shaviv (1994) noted that sub-Coulomb radiative captures and transfer reactions take place mainly when the colliding nuclei are far apart. They argued that since optical models describe well the shapes of the bound state and relative motion wave functions outside the nuclear potential, they should be preferred for extrapolating the laboratory cross sections to solar energies.…”
Section: Nuclear Reaction Ratesmentioning
confidence: 99%
“…1). The inelastic and transfer scattering of deuteron on 7 Li targets has been repeatedly measured in connection with the measurement of the radiative proton capture on 7 Be [23][24][25][26][27][28][29]. The main resonant peak at ∼0.60 MeV above the deuteron+ 7 Li threshold in the 9 Be spectrum (corresponding to deuterons of ∼0.78 MeV kinetic energy), needs to be accurately measured in order to calibrate the mean areal density of 7 Be atoms in the targets used in the proton-capture measurement [30].…”
Section: Introductionmentioning
confidence: 99%